Managing cultural diversity in higher education: Evidence from the University of The Gambia - Lamin Saidyjeng; Banna Sawaneh (Priviet Social Sciences Journal, 2026)
The objective of this study is to examine cultural management at the University of The Gambia (UTG), focusing on institutional policies, management practices, and employees’ perceptions. The research explores how cultural diversity is understood within a higher education context and identifies both its challenges and benefits. A qualitative research design was employed to gain a deeper understanding of how cultural diversity is managed at UTG. Data were collected through semi-structured interviews and open-ended questions administered to administrative and academic staff. Thematic analysis was used to analyze the data and identify key themes related to cultural diversity and its management.The findings reveal that UTG has a culturally diverse workforce in terms of gender, age, educational background, and work experience. Cultural diversity was found to positively contribute to institutional effectiveness by enhancing problem-solving, creativity, decision-making, and cooperation among employees. However, several challenges were also identified, including language barriers, limited awareness of diversity-related policies, and discrepancies between management intentions and employees’ perceptions.The study highlights the need for improved communication, inclusive institutional policies, stronger human resource management practices, continuous training, and increased awareness of diversity management. These measures are essential for effectively managing cultural diversity in higher education institutions. This research contributes to the limited qualitative studies on cultural diversity management in higher education in The Gambia and provides practical insights for university administrators, stakeholders, and policymakers.